1988
DOI: 10.1002/cne.902670408
|View full text |Cite
|
Sign up to set email alerts
|

Topologic and connectional analysis of the dorsal thalamus of Triturus alpestris (Amphibia, Urodela, Salamandridae)

Abstract: A morphological and connectional analysis was performed on the dorsal thalamus of the alpine newt, Triturus alpestris. We have used a graphic reconstruction technique for the evaluation of the connectional (HRP) data. On the basis of these reconstructions, we propose a subdivision of the salamandrid dorsal thalamus into subhabenular, anteroventral, and posterodorsal zones. Each of these zones is defined by its telencephalic projections ("ascending thalamofugal systems"). The posterodorsal zone projects to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 37 publications
4
43
0
Order By: Relevance
“…However, such a projection was not revealed by injection of HRP and HRP-wheat germ agglutinin (WGA) (L. fluviatilis; Polenova and Vesselkin, 1993). Projections from the nucleus dorsalis thalami to the striatum have been shown in amphibians (Wilczynski and Northcutt, 1983;Wicht and Himstedt, 1988;Dubé et al, 1990;Gonzá-lez et al, 1994c;Marín et al, 1997a) and reptiles (Parent, 1976;Lohman and van Woerden-Verkley, 1978;Gonzá lez et al, 1990). The thalamic intralaminar nucleus in mammals sends a prominent projection to the striatum, whereas a minor input is provided by the lateral posterior/pulvinar complex (see Butler, 1994).…”
Section: Striatal Afferents From the Dorsal Thalamusmentioning
confidence: 95%
“…However, such a projection was not revealed by injection of HRP and HRP-wheat germ agglutinin (WGA) (L. fluviatilis; Polenova and Vesselkin, 1993). Projections from the nucleus dorsalis thalami to the striatum have been shown in amphibians (Wilczynski and Northcutt, 1983;Wicht and Himstedt, 1988;Dubé et al, 1990;Gonzá-lez et al, 1994c;Marín et al, 1997a) and reptiles (Parent, 1976;Lohman and van Woerden-Verkley, 1978;Gonzá lez et al, 1990). The thalamic intralaminar nucleus in mammals sends a prominent projection to the striatum, whereas a minor input is provided by the lateral posterior/pulvinar complex (see Butler, 1994).…”
Section: Striatal Afferents From the Dorsal Thalamusmentioning
confidence: 95%
“…Fur thermore, while in most vertebrates almost the entire dorsal thalamus projects heavily to the telencephalon [e.g. see Neary and Northcutt, 1983;Wicht and Himstedt, 1988;Fiebig and Bleckmann, 1989;Wicht and Northcutt, 1989], in teleosts only some parts of the dorsal thalamus seem to project to the telencephalon (see above), and even these connections are difficult to label with even the most sensitive current tech niques.…”
Section: Comparisons To Ollier Vertebratesmentioning
confidence: 99%
“…Knowledge of striatal afferents in urodeles is derived from the work of Kokoros and Northcutt on Ambystoma tigrinum [13], in which the origin of degenerated fibers in the thalamus and mesen cephalic tegmentum after large telencephalic lesions was attributed to the corpus striatum. Recently, Wicht and Himstedt [14] have shown that the thalamostriatal projection originates specifically from the posterodorsal thalamus in Triturus alpestris. In the present study, afferent connections to the corpus striatum have been investigated by retrograde horseradish per oxidase (HRP) transport in a representative urodele, the newt Triturus cristatus.…”
Section: Introductionmentioning
confidence: 99%